2012
DOI: 10.1128/jcm.00621-12
|View full text |Cite
|
Sign up to set email alerts
|

Automated Detection of Toxigenic Clostridium difficile in Clinical Samples: Isothermal tcdB Amplification Coupled to Array-Based Detection

Abstract: dClostridium difficile can carry a genetically variable pathogenicity locus (PaLoc), which encodes clostridial toxins A and B. In hospitals and in the community at large, this organism is increasingly identified as a pathogen. To develop a diagnostic test that combines the strengths of immunoassays (cost) and DNA amplification assays (sensitivity/specificity), we targeted a genetically stable PaLoc region, amplifying tcdB sequences and detecting them by hybridization capture. The assay employs a hot-start isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 36 publications
(32 reference statements)
4
26
0
Order By: Relevance
“…Indeed, 87/90 (96.7%) "lowpositive" samples tested positive by the Portrait test, which is compatible with the expected results. The testing of the "highnegative"-density (C 5 [cell density at which 5% of tests are expected to give a positive result]) samples resulted in 4/90 (4.4%) positive tests, which is consistent with the expected 5% positive samples.…”
Section: Resultssupporting
confidence: 66%
See 4 more Smart Citations
“…Indeed, 87/90 (96.7%) "lowpositive" samples tested positive by the Portrait test, which is compatible with the expected results. The testing of the "highnegative"-density (C 5 [cell density at which 5% of tests are expected to give a positive result]) samples resulted in 4/90 (4.4%) positive tests, which is consistent with the expected 5% positive samples.…”
Section: Resultssupporting
confidence: 66%
“…EIAs directed against C. difficile toxins have reported sensitivities of 25% to 86% (1,5,8,14). Similarly, the reported sensitivities of toxin-based lateral flow tests range from 43% to 73% (3,5,14). Given this low sensitivity, it was suggested that toxin EIAs and lateral flow tests lack utility as confirmatory methods for GDH-positive specimens in two-step testing algorithms (5).…”
mentioning
confidence: 99%
See 3 more Smart Citations